2008
DOI: 10.1590/s0103-50532008000300011
|View full text |Cite
|
Sign up to set email alerts
|

N-Acyl-3,3-difluoro-2-oxoindoles as versatile intermediates for the preparation of different 2,2-difluorophenylacetic derivatives

Abstract: Este trabalho descreve a versatilidade sintética dos derivados N-Acil-3,3-diflúor-2-oxoindóis, obtidos a partir da reação de N-acilisatinas com dietilaminotrifluoreto de enxofre (DAST) que, através da reação com diferentes nucleófilos, promovem a abertura do anel heterocíclico, levando à formação de vários produtos. A reação de N-Acil-3,3-diflúor-2-oxoindóis com água fornece os ácidos 2-(2-N-acilfenil)-2,2-difluoracéticos e com álcoóis fornece os ésteres correspondentes. Reações com aminas e glicina levam à fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The required amino heterocycles 3a – d were prepared according to the methodology described in the literature 14–16…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The required amino heterocycles 3a – d were prepared according to the methodology described in the literature 14–16…”
Section: Resultsmentioning
confidence: 99%
“…It was considered that such products could be obtained from imine precursors. This has been carried out by coupling β‐formylporphyrins 1 and 2 to amino heterocycles, such as the aminotriazole 3a ,14 isoniazid (pyridine‐4‐carbohydrazide, 3b )15 and the aminothiadiazoles 3c and 3d 16 (Figure 1), followed by imine reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel with the application of the α-ketoamide moiety in medicinal chemistry, numerous synthetic methods have been described [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21]. Several authors have demonstrated that the synthesis of the α-ketoamide fragment can be achieved by ring opening of N -acetylisatin ( 1 ) by the attack of an amine at C2-carbonyl group of N -acetylisatin (Scheme 1) [22,23,24,25,26,27]. Recently, Cheah et al [28,29] reported the reaction of N -acetylisatin with L-α-amino acid esters as a novel class of N -glyoxylamide peptide mimics.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with the application of the glyoxylamide in medicinal chemistry, numerous synthetic methods have been described in the literature [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Other authors have also reported that synthesis of the glyoxylamide fragment could be achieved by the ring opening of Nacetylisatin 1 by attacking an amine at C2-carbonyl group of N-acetylisatin (Scheme 1) [27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%